Evaluación del efecto del jugo de pitahaya (Hylocereus triangularis) a diferentes concentraciones sobre el grado de hidratación de las capas superiores de la epidermis, tras realizar una aplicación cutánea única, en sujetos adultos. - Rodas Mancheno, Gabriela Mercedes (2015)
This research has been focused in the study of the moisturizing capability of the pitahaya(Hylocereustriangularis) juice at the upper layers of the epidermis. In order to study the effect of pitahaya on skin hydration in one single application, we began to test gels with different concentrations of the juice from this fruit (0.5%, 1%, 2%, 3%, 4% and 5%), we also used as an instrumental method the electrical capacitance of the skin reading applying the skin’s humidity sensor Scalar Moisture Checker MY-808S. The kinetics over time for the reading of the tested areas was at time zero, 30 minutes, 1 hour, 2 and 5 hours with a total of six hours of continuous study. The skin moisture percentages were measured for each concentration channeled by carbopol gel, demonstrating that the best moisturizing effect occurred at 30 minutes and with a 5% concentration of the pitahaya juice.